Development of an ergonomic child restraint system concept for infants in conventional aircraft seats - Kamarbhari, Syakirah (2018)
The need to provide an ergonomic design of Child Restraint System (CRS) for infants in conventional aircrafts is the subject of much interest and research. Due to the increasing trends of infant passengers traveling by air, the need for an ergonomic design other than the safety aspects alone requires much needed improvement. Even though the safety aspect of the passengers is important, other ergonomic aspects that are lacking such as comfort, usability and convenience of the CRS also contribute to a better travelling environment should have been put into concern as it become essentials in the air transportation industry. Until now, no studies have been reported, specifically on designing the CRS for infants in aircraft, particularly focuses on other ergonomic aspects such as comfort, usability, and convenience, which may benefit both infants and their traveling companion. Hence, this research focuses on developing a new design concept of an Ergonomic CRS for infants in conventional aircraft seats. The objectives of this research are; firstly, to determine the effective criteria of the Ergonomic CRS, secondly, to develop a framework for the design requirement of the Ergonomic CRS. Third, designing a new concept of Ergonomic CRS, and finally, the fourth objective is to evaluate the prototype of an Ergonomic CRS final concept design. The objective was achieved by determining several effective criteria of the Ergonomic CRS, which were based on experienced users‘ perceptions and requirements from the focus group interviews, followed with a framework construction, which were also based on the focus groups and early findings. The conceptual design were generated from the Total Design that executed the integration of brainstorming - TRIZ methodology - methodological chart - weighted objective evaluation. The new design concept was objectively and subjectively evaluated based on the participants‘ responses in three different physical tests, namely; comfort, usability, and convenience test. The focus group findings that were deliberated from six (6) participants in six (6) individual groups have led to a framework development of the requirement criteria that consist of five (5) design requirements, which was proposed to scientifically produce theories as well as methods that can perform as a guideline for the development of CRS for infants in aircrafts. The final design which was selected out of three (3) conceptual designs revealed that the design concept-3 with a value of 4.35 was selected and were developed by using Computer Aided Three-dimensional Interactive Application Software (CATIA). The test reveals that the respondents felt much more attached to their infant when using the newly developed system with 13% higher than the Automotive CRS. The usability test revealed the overall score for the Ergonomic CRS was 14.2% higher than the Automotive CRS. Meanwhile, the convenience test revealed that the score for Ergonomic CRS was 25.4% higher than the Automotive CRS. Overall, the findings on the participants‘ perceptions towards the infant restraint device in conventional aircrafts outlined the most discussed elements of bonding factor, ease of use, and hassle-free, which put into attention to the criteria needed.